A STUDENT PERCEPTIONS REGARDING THE UTILIZATION OF VIRTUAL LABORATORY TO INCREASE INTEREST IN LEARNING CHEMISTRY AT SMAN 3 MATARAM: - - Simanjuntak, Familia Novita; Harefa, Nelius; Azzahra, St. Fatimah; Sumiyati, Sumiyati; Simatupang, Nova Irawati; Sormin, Elferida; Purba, Leony Sanga Lamsari (JCER (Journal of Chemistry Education Research), 2024)
The purpose of this study was to analyze students' perceptions regarding the use of VR-based virtual laboratories inincreasing students' interest in learning chemistry. The research method used is a simple survey method. The researchsample was students from SMAN 3 Mataram, totaling 51 people. Analysis of data from a simple survey using adescriptive quantitative method. The questionnaire instrument is an instrument that is used to collect data anddisseminate it online using the Google Form. The data obtained shows the usefulness, use, responses and advantagesand disadvantages of VR-based virtual laboratories. After conducting the survey, it turned out that the use of VRbasedvirtual laboratories received positive responses and perceptions from students.Key words: Virtual lab, Interests, Online learning